Clinical and Immunological Characteristics of Elderly Onset Rheumatoid Arthritis - LI Zhengfang; WU Chanyuan; MA Mengsi; LI Tingting; WU Xue; MENG Xinyan; ZHANG Sha; WU Lijun (Xiehe Yixue Zazhi)
ObjectiveTo investigate the clinical features and peripheral blood immune cell subsets ofelderly (≥60 years old) onset rheumatoid arthritis (EORA) patients.MethodsThe patients with rheumatoid arthritis (RA) who were hospitalized in the Department of Rheumatology and Immunology of the People's Hospital of Xinjiang Uygur Autonomous Region from March 2023 to December 2023 were selected as the study objects. The demographic data, clinical characteristics, extra-articular manifestations and laboratory examination results of the patients were collected. The patients were divided into EORA group and young adult (< 60 years old)onset rheumatoid arthritis (YORA) group, and the clinical features and peripheral blood immunological indexes of the two groups were compared.ResultsA total of 187 RA patients with an average age of (62.1±12.0) years were enrolled, including 89 patients in the EORA group and 98 patients in the YORA group. Compared with YORA group, EORA group had a higher proportion of male patients(39.3% vs. 22.4%, P=0.012), patients with interstitial lung disease (21.4% vs. 3.1%, P < 0.001), and patients with anemia (10.1% vs. 3.1%, P=0.049).The onset of large joint was more common in the EORA group(53.9% vs. 23.5%, P < 0.001). The number of joint swelling [6(2, 11) vs. 3(1, 7), P=0.002], and the number of tenderness [8(4, 13) vs. 5(3, 9), P=0.001] were also higher in the EORA group. Greater inflammation [C-reactive protein(CRP) : 12.3(3.9, 33.2)mg/L vs. 5.5(1.8, 16.9)mg/L, P=0.000; erythrocyte sedimentation rate(ESR) : 30.5(15.0, 63.0)mm/h vs. 19.0(8.0, 41.0)mm/h, P= 0.006], higher DAS28-CRP score [4.0(2.7, 5.0) vs. 3.2(2.4, 4.9), P=0.002] and DAS28-ESR score [4.3 (2.8, 5.3) vs. 3.4 (2.1, 4.7), P=0.001] were also observed. In terms of peripheral blood immune indexes, the proportion of CD4+T cells in EORA group [(44.5±10.6)% vs. (48.8±10.7)%, P=0.045] was lower than that in YORA group, while the proportion of NK cells [(14.8±8.9)% vs. (10.1±3.7)%, P=0.003] and absolute count [(230.2±156.7)PCS/μL vs. (155.9±106.5)PCS/μL, P=0.014] in EORA group were higher than those in YORA group.ConclusionsCompared with YORA, EORA has higher male proportion, joint disease degree and disease activity. EORA is prone to interstitial lung disease, anemia and high inflammation, and the level of peripheral blood NK cells is higher.